Transformational leadership, group affective tone, and group member social inferences: A leadership complementarity perspective. (13th May 2020) - Bruning, Patrick F.; Turner, Nick; Lin, Hsin‐Chen
Abstract: We investigated how the complementarity between transformational leadership behaviours and group potency predicts changes in group affective tone and subsequent group members' social inferences (job satisfaction, trust in supervisors, and turnover intentions). We analyzed two waves of data from 135 skilled professionals working in 29 groups within a Canadian government agency. Transformational leadership behaviours did not directly relate to changes in group affective tone. However, group potency moderated the relationship between transformational leadership behaviours and group affective tone, as well as the indirect relationships between transformational leadership behaviours and group members' social inferences via group affective tone, such that the relationships were stronger for low‐potency groups. These results suggest transformational leadership may work best when complementing a group's sense of its own perceived capability. Résumé: Dans cet article, nous étudions la manière dont la complémentarité entre les comportements liés au leadership transformationnel et la puissance du groupe prédit les changements dans le climat affectif du groupe et les déductions sociales des membres de celui‐ci (satisfaction au travail, confiance envers les superviseurs et intentions de roulement). 135 professionnels qualifiés travaillant dans 29 groupes au sein d'un organisme gouvernemental canadien y analysent deux vagues de données. Les résultats montrent que les comportements de leadership transformationnel ne sont pas directement liés aux changements observés dans le climat affectif du groupe. Cependant, la puissance du groupe modère la relation entre les comportements de leadership transformationnel et le climat affectif du groupe, ainsi que les relations indirectes entre les comportements de leadership transformationnel et les inférences sociales des membres du groupe via le climat affectif, de sorte que les relations sont plus fortes pour les groupes à faible puissance. Ces résultats suggèrent que le leadership transformationnel fonctionne mieux lorsqu'il complète le sentiment qu'un groupe nourrit sur la perception de sa propre capacité.